1984
DOI: 10.1104/pp.74.4.852
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide-Dependent Oxidation of Flavonols by Intact Spinach Chloroplasts

Abstract: ABSTRACIExternally added quercetin (100 micromolar) was oxidized by intact spinach chloroplasts at a rate of 30 micromoles per mg chlorophyll per hour in the presence of 100 micromolar H202. The oxidation rate was increased by about 20% in a hypotonic reaction mixture. The thylakoid fraction also oxidized the flavonol in the presence of H202, and the rate was about 25% of that by intact chloroplasts. The oxidation of quercetin was inhibited by KCN and NaN3. Ascorbate, which permeates slowly across chloroplast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…On the other hand, several reports have suggested that the surface localization of flavonoids improves their antioxidant potential by blocking the interaction of free radicals with the membrane lipids, efficiently preventing peroxidation (Moliveanu et al, 2000;Erlejman et al, 2004;Oteiza et al, 2005). In addition, the investigations with intact chloroplasts and thylakoids showed that the exogenously added quercetin delays lipid peroxidation (Takahama, 1983(Takahama, , 1984Chanhan et al, 1992), suppresses carotenoid and chlorophyll photobleaching and prevents D1 protein degradation under abiotic stress (Singh and Singhal, 1999). As can be seen in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, several reports have suggested that the surface localization of flavonoids improves their antioxidant potential by blocking the interaction of free radicals with the membrane lipids, efficiently preventing peroxidation (Moliveanu et al, 2000;Erlejman et al, 2004;Oteiza et al, 2005). In addition, the investigations with intact chloroplasts and thylakoids showed that the exogenously added quercetin delays lipid peroxidation (Takahama, 1983(Takahama, , 1984Chanhan et al, 1992), suppresses carotenoid and chlorophyll photobleaching and prevents D1 protein degradation under abiotic stress (Singh and Singhal, 1999). As can be seen in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The reaction was initiated by the addition of glucose oxidase (1 g ml Ϫ1 ) which allowed the generation of H 2 O 2 at 0.37 M s Ϫ1 . The oxidation of phenols was followed spectrophotometrically using a UV-160A spectrophotometer (Shimadzu, Kyoto, Japan) by monitoring a decrease in absorbances at 380, 310 and 260 nm for quercetin, ferulic acid (FA) and coniferyl alcohol (CA), respectively, using absorption coefficients of 8.7 (quercetin), 11.3 (FA) and 7.5 (CA) mM Ϫ1 cm Ϫ1 (36,37). At the same time, the oxidation rate of NADH was determined by following a decrease in the absorbance at 340 nm using an absorption coefficient of 6.2 mM Ϫ1 cm Ϫ1 (5).…”
Section: Methodsmentioning
confidence: 99%
“…This transfers the problem of scavenging from 02^ to H2O2, implying that none of the mechanisms is sufficient, and creating a need for alternative or additional peroxidase capacities. While no such models have been proposed using any species, peroxide-dependent oxidation of phenolics has been studied in spinach, both in chloroplasts and in the apoplast of leaves (Takahama 1984;Takahama & Oniki 1992), and R. stylosa leaves contain up to 20% by dry weight of such compounds, particularly under stressed conditions (Robertson 1988;Lovelock, Clough & Woodrow 1992).…”
Section: Discussionmentioning
confidence: 99%